X-Linked Lissencephaly With Absent Corpus Callosum and Abnormal Genitalia: An Evolving Multisystem Syndrome With Severe Congenital Intestinal Diarrhea Disease. Issue 1 (7th November 2017) - Coman, David; Fullston, Tom; Shoubridge, Cheryl; Leventer, Richard; Wong, Flora; Nazaretian, Simon; Simpson, Ian; Gecz, Josef; McGillivray, George
X-linked lissencephaly with abnormal genitalia is a rare and devastating syndrome. The authors present an infant with a multisystem phenotype where the intestinal manifestations were as life limiting as the central nervous system features. Severe chronic diarrhea resulted in failure to thrive, dehydration, electrolyte derangements, long-term hospitalization, and prompted transition to palliative care. Other multisystem manifestations included megacolon, colitis, pancreatic insufficiency hypothalamic dysfunction, hypothyroidism, and hypophosphatasia. A novel aristaless-related homeobox gene mutation, c.1136G>T/p.R379L, was identified. This case contributes to the clinical, histological, and molecular understanding of the multisystem nature of this disorder, especially the role of ARX in the development of the enteroendocrine system.